Sentiment analysis of political figure glorification on social media - Juwandi; Haris Herdiansyah (Universitas Sarjanawiyata Tamansiswa, 2025)
In the digital age, when access to knowledge is widespread, many assume that society will become more logical, critical, and objective, thereby reducing the glorification of public figures. In fact, glorification has found an even broader place in the digital age. Although there are many public opinions and media reports about the glorification of political figures, systematic studies to understand this phenomenon are very limited. This study aims to analyze the glorification of political figures on social media using sentiment analysis. A total of 8,000 tweets were analyzed. The results show that the majority of tweets contain positive sentiments, namely 4,200 tweets or 52.5% of the total data, indicating the glorification of political figures. The glorification found was Overgeneralization (22%), Hero Worship (15%), and Dismissive of Criticism (12%). The glorification patterns that often appear were not based on objective facts, where political figures were positioned as ideal figures beyond criticism. This study contributes to the study of political psychology and public communication in the digital age, particularly regarding how emotions influence the image of political figures. This study highlights the importance of improving digital literacy and critical thinking in order to filter content that contains excessive adoration of political figures, which can have a negative impact on social cohesion, the quality of democracy, and public accountability